Proceedings of the ACM Conference on Bioinformatics, Computational Biology and Biomedicine 2012
DOI: 10.1145/2382936.2382967
|View full text |Cite
|
Sign up to set email alerts
|

A volumetric method for representing and comparing regions of electrostatic focusing in molecular structure

Abstract: Algorithms for protein structure comparison employ diverse and effective representations of molecular shape. However, they do not generally represent the shape of the electrostatic potential field, except at the molecular surface. This approach neglects the geometry of the field on the outside of the molecular surface, where electrostatic focusing can play an important role in molecular recognition: Narrow clefts and grooves can partially shield charged atoms from the high dielectric solvent, enhancing potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…In this section, we first paraphrase our earlier results that demonstrate the accuracy of our methods for identifying regions of electrostatic focusing [11]. In sections 4.1 and 4.2, we show that our methods identify previously documented regions of electrostatic focusing in protein, on a small scale, and DNA, on a large scale.…”
Section: Resultsmentioning
confidence: 59%
See 2 more Smart Citations
“…In this section, we first paraphrase our earlier results that demonstrate the accuracy of our methods for identifying regions of electrostatic focusing [11]. In sections 4.1 and 4.2, we show that our methods identify previously documented regions of electrostatic focusing in protein, on a small scale, and DNA, on a large scale.…”
Section: Resultsmentioning
confidence: 59%
“…In earlier work, we demonstrated that three dimensional solids could be used to represent and compare regions of electrostatic focusing [11]. Applying this approach to the analysis of protein and DNA structures, we verified, using Boolean set operations [10] (Figure 1), that it correctly identified focusing regions, in proteins and DNA, discussed in the literature.…”
Section: Introductionmentioning
confidence: 58%
See 1 more Smart Citation